Commentary on "Can a good philosophical contribution be made just by asking a question?". (5th December 2022) - Habgood‐Coote, Joshua; Watson, Lani; Whitcomb, Dennis
Abstract: This paper explains some of the reasoning behind "Can a Good Philosophical Contribution Be Made Just by Asking a Question?, " a paper which consists solely in its title and which is published in the same issue of the journal as the present paper. The method for explaining that reasoning consists in making available a lightly edited version of a letter the authors sent to the editors when submitting the title‐only paper. The editors permitted publication of that paper on the condition that the authors also separately publish a version of that letter; the present paper aims to fulfil that condition.